O estudo das topologias básicas de conversores híbridos CC-CC impedância série - Cunha, Vagner Maciel (2022)
This work contains the study of basic topologies of hybrid converters classified as serious impedance, the converters presented here are said to be hybrid because they associate two technologies, the switched converters and the linear amplifiers, the objective here is to extract the best in each structure, to get from amplifiers responses with high speed and without distortion (high fidelity) and from switched converters the ability to bring greater energy density to the load. There are several ways to associate both Technologies. The switched converter, the load and the linear amplifier can be placed in parallel or in series, the linear amplifier may or may not have a power source, when the amplifier does not have a power source, linear uses energy from the switched converter. This dissertation deals with a series association and with the sourceless linear amplifier, with these characteristics the linear amplifier can be observed as an impedance. A general study carried out on both technologies is presented. On the MOSFET amplifiers, the characteristics (structure, form of construction and the physical phenomena present), the forms of operation (operation points such as cuts, triode and saturation, identifying at this moment what is the linear region and how to maintain the operation in this region), the limitations (such as threshold voltage, capacitive and resistive couplings and the dependence of the gain in relation to the drain current) and finally a methodology for projects of MOSFET amplifiers controlled by operational amplifiers. The design of each of the hybrid converters is demonstrated followed by an analysis carried out through the simulations responses, at the end the experimental design is presented, for which the Buck converter was chosen, then an analysis of the results of this experiment follows.